ANALISIS STRATEGI PENGHIMPUNAN ZAKAT PROFESI DI BAZNAS BONDOWOSO PADA ERA DIGITALISASI - Siti Habibatur Rahma; Lutfi, Lutfiatul Hasanal (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This study aims to answer the question of how the professional zakat collection strategy of BAZNAS Bondowoso is implemented in the digital era, which is characterized by changes in social interactions and the increasing use of financial technology. This study is based on the background that professional zakat is one of the greatest potential drivers of national economic development, but often faces difficulties in implementation due to a lack of zakat literacy and a variety of payment service options. The purpose of this study is to examine the collection practices carried out by regional zakat institutions by examining the social and cultural context of the local community. This research methodology uses a qualitative descriptive study approach using data from BAZNAS administrators, field observations, and analysis of supporting literature. The study findings indicate that BAZNAS Bondowoso implements direct fundraising strategies such as institutional connections, mentoring muzakki, and face-to-face socialization, as well as indirect fundraising strategies through digital channels such as bank transfers, sharia payment applications, and the official BAZNAS platform. Digital strategies are used to increase efficiency, convenience, and reach of muzakki, while personal strategies are used to maintain trust and social cohesion. This study contributes to the development of a flexible, inclusive, and progressive professional zakat collection model in the digital era.